Dream ‘n’ Go Enterprise / Muhammad Akif Afif Azman…[et al.] - Azman, Muhammad Akif; Chokkeri, Mohammad Syazrul Nazmi; Kamarol Hisham, Nur Khalyda; Mohd Nazri, Nur Syahirah Nasuha; Abdul Aziz, Nurul Atikah; Saidin, Nurul Syahirah (2019)
To start up a business of course the main thing we need is fund or money as the capital. We can get the fund through a few parties for examples bank, financial institution and also investors. Investors can provide valuable contacts, useful advice and motivation to work harder at growing the business, in addition to providing the funding. Those financial institutions need to see the plan to determine whether the business idea is viable. So, business plan that have good idea and potential of success in the market will attract the investor to invest and also give confidence and trust from the bank in term of taking business loan from them.